1999
DOI: 10.1017/s0142716499002039
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with foreign language anxiety

Abstract: Foreign language anxiety is a complex phenomenon that has been found to be a predictor of foreign language achievement. This study of 210 university students examined factors that predict1 foreign language anxiety. A setwise multiple regression analysis revealed that seven variables (i.e., age, academic achievement, prior history of visiting foreign countries, prior high school experience with foreign languages, expected overall average for current language course, perceived scholastic competence, and perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
231
1
11

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(270 citation statements)
references
References 54 publications
27
231
1
11
Order By: Relevance
“…It is indicated that foreign language anxiety is different from ordinary anxiety, proper to the situation, that it emerges in foreign language courses and affects students achievement adversely. It is widely accepted (Onwuegbuzie et al, 1999) that foreign language anxiety has a negative effect on students achievement in foreign language courses.…”
Section: Discussion Theory and Practice In Language Studies © 201mentioning
confidence: 99%
“…It is indicated that foreign language anxiety is different from ordinary anxiety, proper to the situation, that it emerges in foreign language courses and affects students achievement adversely. It is widely accepted (Onwuegbuzie et al, 1999) that foreign language anxiety has a negative effect on students achievement in foreign language courses.…”
Section: Discussion Theory and Practice In Language Studies © 201mentioning
confidence: 99%
“…For instance, Matsuda and Gobel's (2004) research on language anxiety and performance in the foreign language classroom reported that self-confidence is an important factor in language performance in the classroom of first-year college students in Japan. In addition, Onwuegbuzie, Bailey, and Daley (1999) and Casado and Dereshiwsky (2004) found the same results examining university students' language learning and language anxiety-self-confidence is the key to language learning.…”
Section: Self-confidencementioning
confidence: 64%
“…Other studies also support the belief that self-confidence is an important factor for successful language learning (e.g., Casado & Dereshiwsky, 2004;Ehrman & Oxford, 1995;Matsuda & Gobel, 2004;Onwuegbuzie, Bailey, & Daley, 1999, 2000Ro, 2013). For instance, Matsuda and Gobel's (2004) research on language anxiety and performance in the foreign language classroom reported that self-confidence is an important factor in language performance in the classroom of first-year college students in Japan.…”
Section: Self-confidencementioning
confidence: 78%
See 1 more Smart Citation
“…Statistics anxiety may be a critical factor in influencing and attaining a student's academic and vocational goals' [4] . A large body of empirical research to-date has documented a strong and consistent negative association between statistics anxiety on the one hand and academic performance on the other [7,8,11,13,14] . However, it can be argued that statistics anxiety is not necessarily a demotivating factor resulting in lower achievements.…”
Section: Introductionmentioning
confidence: 99%